The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5562/cca3668
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazolium Ionic Liquid Immobilized on Periodic Mesoporous Organosilica as an Effective Reusable Catalyst for Chemical Fixation of CO2 into Cyclic Carbonates

Abstract: A type of dichloro(dimethoxyethane)nickel anionic benzotriazolium ionic liquid-functionalized periodic mesoporous organosilicas were synthesized and tested as effective and practical heterogeneous catalysts in the cycloaddition of CO2 with epoxides. The catalyst PMO@ILC4H10O2NiCl3(1.0) showed brilliant catalytic activity for the synthesis of cyclic carbonates with high yields and selectivities under solvent-and cocatalyst-free conditions. We also found that the catalytic activity could be significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In addition, as the aforementioned Co-PMO-IL(x), 150 NiCl 2 (DME) (DME = 1,2-dimethoxyethane) reacted with PMO-IL to form NiCl 3 (DME) − anionic benzotriazolium ionic liquid-functionalized periodic mesoporous organosilicas PMO@ILC 4 H 10 O 2 NiCl 3 with various IL contents. 176 The catalytic activity was evaluated by the cycloaddition of CO 2 with epoxides ( Scheme 13 ). The results showed that catalysts PMO@ILC 4 H 10 O 2 NiCl 3 with various IL contents were effective and practical heterogeneous catalysts in the synthesis of cyclic carbonates with high yields (89.5–97.6%) and selectivities (>99%) under solvent- and cocatalyst-free conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as the aforementioned Co-PMO-IL(x), 150 NiCl 2 (DME) (DME = 1,2-dimethoxyethane) reacted with PMO-IL to form NiCl 3 (DME) − anionic benzotriazolium ionic liquid-functionalized periodic mesoporous organosilicas PMO@ILC 4 H 10 O 2 NiCl 3 with various IL contents. 176 The catalytic activity was evaluated by the cycloaddition of CO 2 with epoxides ( Scheme 13 ). The results showed that catalysts PMO@ILC 4 H 10 O 2 NiCl 3 with various IL contents were effective and practical heterogeneous catalysts in the synthesis of cyclic carbonates with high yields (89.5–97.6%) and selectivities (>99%) under solvent- and cocatalyst-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As the aforementioned PMO@ILC 4 H 10 O 2 NiCl 3 , 176 copper oxychloride (Cu 2 (OH) 3 Cl) was linked to benzotriazolium ionic liquid-modified PMO (PMO-IL) to afford PMO@ILCu 2 (OH) 3 Cl 2 ( x ) ( x represents the amount of IL used in preparation) with ion-type unit –IL + [Cu 2 (OH) 3 Cl 2 ] − . These catalysts were used for the cycloaddition of CO 2 with epoxides.…”
Section: Introductionmentioning
confidence: 99%